Association of Polymorphisms in Oxidative Stress Genes with Clinical Outcomes for Bladder Cancer Treated with Bacillus Calmette-Guérin - Wei, Hua; Kamat, Ashish; Chen, Meng; Ke, Hung-Lung; Chang, David W.; Yin, Jikai; Grossman, H. Barton; Dinney, Colin P.; Wu, Xifeng (PLOS ONE, 2012)
Genetic polymorphisms in oxidative stress pathway genes may contribute to carcinogenesis, disease recurrence, treatment response, and clinical outcomes. We applied a pathway-based approach to determine the effects of multiple single nucleotide polymorphisms (SNPs) within this pathway on clinical outcomes in non-muscle-invasive bladder cancer (NMIBC) patients treated with Bacillus Calmette-Guérin (BCG). We genotyped 276 SNPs in 38 genes and evaluated their associations with clinical outcomes in 421 NMIBC patients. Twenty-eight SNPs were associated with recurrence in the BCG-treated group (P<0.05). Six SNPs, including five in NEIL2 gene from the overall and BCG group remained significantly associated with recurrence after multiple comparison adjustments (q<0.1). Cumulative unfavorable genotype analysis showed that the risk of recurrence increased with increasing number of unfavorable genotypes. In the analysis of risk factors associated with progression to disease, rs3890995 in UNG, remained significant after adjustment for multiple comparison (q<0.1). These results support the hypothesis that genetic variations in host oxidative stress genes in NMIBC patients may affect response to therapy with BCG.